The Prognostic and Therapeutic Value of the Mutational Profile of Blood and Tumor Tissue in Head and Neck Squamous Cell Carcinoma. (20th November 2020) - Wilson, Harper L.; D'Agostino, Ralph B.; Meegalla, Nuwan; Petro, Robin; Commander, Sara; Topaloglu, Umit; Zhang, Wei; Porosnicu, Mercedes
Abstract: Background: The purpose of this study was to explore the genomic landscape of head and neck squamous cell carcinoma (HNSCC) in circulation (circulating tumor DNA [ctDNA]) and tumor (tumor tissue DNA [tDNA]) and understand the implications of ctDNA sequencing for prognosis and precision oncology treatments. Materials and Methods: This is a retrospective review of 75 patients with HNSCC for both tDNA and ctDNA. Results were analyzed for concordance between tDNA and ctDNA and for their individual and combined association with demographics, survival, and presence and extent of disease at last visit (DLV). Results: The five most frequently altered genes were TP53, CDKN2A, TERT, BRCA2, and NOTCH1 . Twenty percent of patients had NOTCH1 alterations in tDNA, with none found in ctDNA. Concordance among altered genes was 13.0%, and 65.3% of patients had actionable ctDNA alterations. ctDNA alterations were significantly associated with decreased overall survival (OS) and presence and extent of DLV. In DNA repair genes, alterations in ctDNA alone and combined with tDNA were significantly associated with decreased OS and presence of DLV. Similar significant associations were found in TP53 for ctDNA alone and combined with tDNA. DNA repair gene alterations in ctDNA and unique ctDNA alterations within partially concordant genes were significantly associated with decreased OS in multivariate analysis. Conclusion: This study illustrates the circulating and tumor genomic profile in the largest HNSCC cohort to date, underscoring the potential utility of ctDNA in prognostication and precision oncology treatment. For the first time, the presence of ctDNA alterations and specific ctDNA sequencing results were shown to be significantly associated with poor prognosis in HNSCC. Implications for Practice: The use of precision genomic targeted therapies in head and neck squamous cell carcinoma (HNSCC) lags behind many other cancers, and poor survival in advanced stages indicates the urgent need for improved treatment options. This exploratory analysis of circulating tumor DNA (ctDNA) and tumor tissue DNA (tDNA) sequencing in the largest cohort to date of patients with HNSCC provides a novel depiction of the ctDNA genome, with two thirds of patients having actionable ctDNA alterations. This study reports for the first time the prognostic value of ctDNA sequencing, with the presence of ctDNA alterations, specific ctDNA alterations in DNA repair genes and TP53, and unique ctDNA alterations within partially concordant genes predicting poor survival. Abstract : This article reports on the genomic landscape of circulating tumor DNA in head and neck squamous cell carcinoma and analyzes its prognostic significance and potential contribution to precision oncology treatment strategies alone and in combination with tumor DNA analysis.